THE ROLE OF ILQĀ' MUFRADĀT ACTIVITIES IN DEVELOPING FEMALE STUDENTS' STIT MADANI YOGYAKARTA ARABIC SPEAKING SKILLS - Faiza Alifia Ahmad; Ghaziatus Sifa; Zulkifli Hayad (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The purpose of this study is to determine the role of ilqā’ al-mufradāt activities in improving students' ability to communicate in Arabic within the university environment. One method of learning vocabulary is through ilqā’ al-mufradāt, which involves introducing new vocabulary, collective pronunciation, transcription, repetition, memorization, and sentence construction (jumlah mufīdah). This study employed a descriptive qualitative method, with data collected through documentation and interviews. The results show that ilqā’ al-mufradāt plays an important role in enhancing vocabulary mastery at the cognitive level, which serves as the foundation for developing speaking skills. Students find it easier to recognize and remember new vocabulary and begin to get used to forming simple sentences. However, vocabulary acquisition alone has not directly improved speaking fluency. The study suggests the need for more communicative, interactive, and contextual teaching methods. Identified obstacles include limited contextual application, a learning environment that does not fully support active Arabic practice, and students’ low confidence in using the language.